An investigation on the efficiency of internal auditing in risk management: a case of city of Mutare - Matenhese, Dwright (Midlands State University, 2017)
The central point of this research is to investigate the efficiency of internal audit in risk management. Mutare City Council was used as the case in this research. This was necessitated by the fact that the council has been a victim of corrupt tendencies and theft, operational costs have increased and service delivery has declined leading to ratepayer dissatisfaction. The researcher in trying to come up with relevant information made a critical review on the relevant literature related to the aforementioned problem. The literature was mainly centered on the role of internal audit in risk management. The research methodology used by the researcher was quantitative and qualitative in nature. The data collection process included the administering of questionnaires and an interview to extract the relevant data for analysis. The data collected was analysed qualitatively in such a way that the relevant results were obtained. The findings made by the researcher were presented, analysed and appropriate recommendations were suggested. The research found out that the efficiency of the internal audit in risk management is hindered because of various factors that affect the function. Furthermore, resources are a major impediment in the internal audit department of City of Mutare in trying to achieve its goals.